The Application of The Course Review Horay (CRH) Cooperative Learning Model to Understanding The Concept of Mathematics of Class VIII Students of SMPN 2 Sijunjung - Siregar, Majidah Khairani; Febrinal, Dian (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2020)
This study is based on the fact that there is not in accordance with what is expected that the understanding of mathematics concepts of students of class VIII SMPN 2 Sijunjung lesson year 2019/2020 is still lacking. This is caused by the learning process that takes place in the classroom does not actively involve students. Efforts that can be done is to apply cooperative learning model Course Review Horay type (CRH). The purpose of this study was to determineÂ whether the understanding of mathematics concepts of grade VIII students of SMPN 2 Sijunjung by using cooperative learning model of Course Review Horay (CRH) type is better than understanding students' mathematical concept using conventional learning. The data of this research is the final test data of students' mathematical concepts comprehension obtained by giving test to the two sample classes. From the results of the t-test hypothesis analysis, it was obtained tcount = 1.936 and ttable = 1.669, so it can be concluded that the understanding of the mathematical concepts of students by using Cooperative Learning Model Course Course Horay Type (CRH) is better than the conventional learning model in students of grade VIII SMPN 2 Sijunjung.